Pré-tratamento ácido e hidrólise enzimática em folhas de mandioca para a obtenção de etanol de segunda geração - Torraca, Raphael Sarraf Martins (2019)
This work proposes the use of cassava leaves as a means of obtaining Total Reducing Sugars (TRS) for the production of second generation ethanol. For this, the biomass characterization was performed by determining the ash, extractive and lignin contents, the acid pretreatment and then the enzymatic hydrolysis. The determination of reducing sugars obtained during pretreatment was performed by 3,5-dinitrosalicylic acid (DNS) and by high performance liquid chromatography by pulsed amperometric detection for carbohydrates. Initially, an experimental design was carried out from a Central Composite Rotational Design (CCRD) to determine pretreatment conditions. The independent variables studied by CCRD were sulfuric acid concentrations (1 to 3%) and solids loading (5 to 20%) and the TRS response variable. Then, statistical modeling was used to calculate the effects of variables, the elaboration of predictive models and ANOVA, and the confidence level for the model is 95%. Through the analysis of the response surface and the contour curve, the optimum point of 3% H2SO4 and 20% solids was obtained, which were used to perform a new pretreatment in the optimal condition and then to enzymatic hydrolysis, determining the TRS by DNS methodology. The concentrations obtained from Total Reducing Sugars were 55.2g/L for acid pretreatment and 8.89g/L for enzymatic hydrolysis.